Pengaruh Pengetahuan Investasi Dan Literasi Keuangan Terhadap Minat Berinvestasi Di Pasar Modal Dengan Perkembangan Teknologi Digital Sebagai Variabel Moderasi - Muthia Willi Amanda; Mondra Neldi; Putri Azizi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine the influence of Investment Knowledge and Financial Literacy on Investment Interest in the Capital Market with the Development of Digital Technology as a Moderating Variable. The population of this study is students of the Faculty of Economics and Business, Universitas Putra Indonesia